Audio Images: Analyzing impingement sounds of an air jet to develop a new tool wear measurement system - Würschinger, Hubert; Hanenkamp, Nico (Measurement, 2025)
Cutting tools are essential in machining processes, where knowing the condition of the tool is crucial to determining the optimal time for replacement. Various methods exist to assess tool condition, yet they are rarely applied due to challenges users face with these systems. This article provides background on a new approach for assessing and measuring tool wear using the impingement sound of an air jet. By scanning the surface with an air jet, an Audio Image is generated, enabling the reconstruction of surface details and the analysis of height variations, edges, and wear characteristics. Changes in the sound spectrum provide insights into surface variations, height differences, edge detection, and wear patterns. These findings open new possibilities for developing a Tool Condition Monitoring (TCM) system capable of reconstructing wear in three dimensions, offering more detailed and cost-effective analysis compared to existing methods.
CRIS-Team Scopus Importer:2025-02-17